PENGARUH KEMANDIRIAN BELAJAR DAN PERHATIAN ORANG TUA SISWA KELAS IV SD NEGERI KECAMATAN BATU SOPANG TERHADAP HASIL BELAJAR IPAS - Suliyono; A.A.Ketut Budiastra; Hari Wahyono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the effect of learning independence on the science learning outcomes of fourth-grade students at SDN Batu Sopang District and to analyze the effect of parental attention on the science learning outcomes of fourth-grade students at SDN Batu Sopang District. This study uses a quantitative approach with a correlational design. Data collection uses a questionnaire for the variables of learning independence and parental attention, while science learning outcomes use student learning outcome scores. The sample used in this study was 212 fourth-grade students. The validity test of the instrument used person's product moment correlation, while the reliability test used Alpha Cronbach. The data obtained were analyzed using simple and multiple linear regression techniques, as well as one-way ANOVA. The results of the study indicate that there is a significant positive effect between the learning independence variable on science learning outcomes of 0.182 with a t count of 2.667 and a significance value of 0.008 <0.05. There is a significant positive influence between the variable of parental attention on science learning outcomes of 0.191 with a t count of 2.809 and a significance value of 0.005 <0.05.